Case report: Rare benign obstructive disease of the biliary tract—a rare case of eosinophilic cholangitis - Huang, Xiao-Ning; Fang, Qi-Min; Zhong, Yu-Feng; Liu, Jing (Frontiers in Medicine, 2024)
Object: Eosinophilic cholangitis (EC) is an uncommon form of benign biliary obstruction. It frequently eludes accurate clinical diagnosis, leading to inappropriate treatment methods. It is our aspiration that this clinical report will impart comprehensive insights into EC and, specifically, the critical role of tomographic examination. Case Summary: A 34-year-old manwas urgently admitted to the hospital due to excruciating abdominal distress persisting for several hours. Following a six-day course of anti-inflammatory therapy, his symptoms displayed marginal improvement, prompting his discharge. He returned to the hospital a month later for re-examination on doctor's orders.Based on the results of the re-examination, the patient refused steroid hormone shock therapy and subsequently underwent laparoscopic left-lateral hepatic lobectomy in order to confirm the diagnosis. The preoperative absolute counts of eosinophils in the peripheral blood were documented as 2.3×10^9/L, 3.06×10^9/L, and 1.50×10^9/L consecutively; concurrently, the corresponding percentages of eosinophils were quantified at levels of 21.90%, 30.70%, and 19.20%. The subsequent postoperative pathological assessment unveiled EC as the definitive diagnosis. The patient has since remained free from disease recurrence and is presently alive. Conclusion: When encountering a patient presenting with persistent elevation in absolute eosinophil count in peripheral blood, coupled with imaging manifestations suggestive of intrahepatic periductal inflammation, diagnosis of EC should be highly suspected. The most optimal diagnostic and therapeutic workflow for EC could entail CT-guided liver lesion biopsy, ensued by glucocorticoid pulse therapy, and finally, shortterm monitoring utilizing CT or MRI (including T1WI, T2WI, DWI, CEMRI) techniques.